Total quality management for site supervision / Muhammad Aiman Abd Jaafar - Abd Jaafar, Muhammad Aiman (Universiti Teknologi MARA, Perak, 2019)
Total quality management in construction ensures quality and productivity. It was basically a way of thinking about the concept, visualization and achievement of goals. TQM was a concept in which organizations, processes and people are interwoven in the correct format so that right things were done rightly at the correct time. TQM gave emphasis on innovation and adaptation of new technology to improve quality. The aim was to improve an organization's ability to deliver quality to its customers on a continuously improving basis. The data were collected by observations on site, documents review and interviews session. The results that can be gained by the supervision was improvised the project with the references from the master work program and how its helps to the completion of project. And also, the issue and problems while carried out inspections and confronts with workers and suppliers can be solved by referred the TQM. Those problems occur and the TQM gave the solution on how to fix it. All those things were important to ensured the QA and QC aspects in the TQM achieved the target for the project.